Phenotypic characterization of spatial immune infiltration niches in non-small cell lung cancer - Anna Sandström Gerdtsson; Mattis Knulst; Johan Botling; Artur Mezheyeuski; Patrick Micke; Sara Ek (OncoImmunology)
The immune microenvironment of non-small cell lung cancer (NSCLC) is heterogeneous, which impedes the prediction of response to immune checkpoint inhibitors. We have mapped the expression of 49 proteins to spatial immune niches in 33 NSCLC tumors and report key differences in phenotype and function associated with the spatial context of immune infiltration. Tumor-infiltrating leukocytes (TIL), identified in 42% of tumors, had a similar proportion of lymphocyte antigens compared to stromal leukocytes (SL) but displayed significantly higher levels of functional, mainly immune suppressive, markers including PD-L1, PD-L2, CTLA-4, B7-H3, OX40L, and IDO1. In contrast, SL expressed higher levels of the targetable T-cell activation marker CD27, which increased with a longer distance to the tumor. Correlation analysis confirmed that metabolic-driven immune regulatory mechanisms, including ARG1 and IDO1, are present in the TIL. Tertiary lymphoid structures (TLS) were identified in 30% of patients. They displayed less variation in the expression profile and with significantly higher levels of pan lymphocyte and activation markers, dendritic cells, and antigen presentation compared to other immune niches. TLS also had higher CTLA-4 expression than non-structured SL, which may indicate immune dysfunction. Neither the presence of TIL nor TLS was associated with improved clinical outcomes. The apparent discrimination in functional profiles of distinct immune niches, independent of the overall level of leukocytes, illustrates the importance of spatial profiling to deconvolute how the immune microenvironment can dictate a therapeutic response and to identify biomarkers in the context of immunomodulatory treatment.